IMPLEMENTASI PEMBELAJARAN IPS BERBASIS APLIKASI QUIZIZZ PADA PEMBELAJARAN ABAD 21 DI SD NEGERI 89 PALEMBANG - Rina Dianti; Endie Riyoko; Kabib Sholeh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
With the rapid development of technology in the world of education today, it can make it easier for an educator in the teaching and learning process because of the use of sophisticated learning media in the form of Quizizz application learning media technology. The purpose of this study was to find out the steps for implementing quizizz application-based learning in 21st century social studies learning at SD Negeri 89 Palembang and to find out the results of evaluating the implementation of quizizz application-based learning for 21st century social studies using swot analysis at SD Negeri 89 Palembang. The research method used is a qualitative type with a descriptive nature. This study uses data collection techniques through observation, interviews and documentation. The results of this study are, the steps in the implementation of quizizz application-based learning in the 21st century social studies learning are in the form of the planning stage, the preparation stage, the implementation stage and the learning evaluation stage. There is an analysis of the results of the evaluation of implementation based on the quizizz application in social studies learning in the 21st century using SWOT analysis, namely there are 4 things which include strengths, one of which is making students not bored in participating in the learning process, Weaknesses depending on the internet network, Opportunities, one of which is in the form of students being able to develop with educational patterns that use technology, threats (Threaths), one of which is making students lazy to open and read books.